A GIS-Based Assessment of Attributes Affecting Publicness of Urban Open Spaces - Das, Subrata; Moon, Farha; Dey, Gourpada; Das, Mohona; Paul, Rina (Journal of Architectural/Planning Research and Studies (JARS), 2025)
Urbanisation is rapidly reducing open spaces, while the remaining urban open areas often need better qualities to transform them into inclusive public places. This study examines the effect of key factors such as accessibility, ownership, management, control, facility provision, and naturalness on publicness perception. Socio-political and physical attributes of the open spaces were recorded during field surveys and structured as geospatial data in GIS for geostatistical analysis. The findings reveal that accessibility and management significantly enhance publicness. On the other hand, natural features and government ownership negatively correlate with publicness due to the underutilisation of natural elements and strict access controls at government-owned open spaces. To address these gaps, this study recommends improving accessibility, adopting better management practices, reducing restrictions, and integrating natural features into open-space design. By combining empirical evaluations with GIS-based spatial analysis, this research presents actionable strategies to enhance the publicness of urban open spaces.